2017
DOI: 10.3892/mmr.2017.7999
|View full text |Cite
|
Sign up to set email alerts
|

High expression of long non‑coding HOTAIR correlated with hepatocarcinogenesis and metastasis

Abstract: HOX transcript antisense RNA (HOTAIR), a newly discovered long noncoding RNA (lncRNA), has been reported to be a poor prognostic marker in many types of cancers. The current study attempted to investigate the biological roles and clinicopathlogical implications of HOTAIR in hepatocellular carcinoma (HCC), as well as understand the molecular mechanisms of HOTAIR in HCC progression. HOTAIR expression in 95 HCC patients with paired HCC tissues and adjacent non‑cancer tissues were investigated using quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Several studies showed that HOTAIR levels are elevated in HCC [ 82 , 83 , 84 , 85 , 86 , 87 ], and that its expression is associated with patients with increased risk of recurrence or metastasis [ 82 , 86 ], poor prognosis [ 84 ] and significantly shorter recurrence-free survival [ 83 ]. At the cellular level, HOTAIR is involved in proliferation, cell motility, viability and invasion, cell cycle progression, apoptosis, autophagy, and chemotherapeutic sensitivity of cancer cells to cisplatin and doxorubicin [ 83 , 84 , 85 , 86 , 87 , 88 , 117 , 118 , 119 , 120 ].…”
Section: Widespread Lncrna Dysregulation In Hccmentioning
confidence: 99%
“…Several studies showed that HOTAIR levels are elevated in HCC [ 82 , 83 , 84 , 85 , 86 , 87 ], and that its expression is associated with patients with increased risk of recurrence or metastasis [ 82 , 86 ], poor prognosis [ 84 ] and significantly shorter recurrence-free survival [ 83 ]. At the cellular level, HOTAIR is involved in proliferation, cell motility, viability and invasion, cell cycle progression, apoptosis, autophagy, and chemotherapeutic sensitivity of cancer cells to cisplatin and doxorubicin [ 83 , 84 , 85 , 86 , 87 , 88 , 117 , 118 , 119 , 120 ].…”
Section: Widespread Lncrna Dysregulation In Hccmentioning
confidence: 99%
“…“HOX transcript antisense intergenic RNA” or HOTAIR is a lncRNA (2.2 kb length) which originates from the HOXC antisense strand [ 23 ]. HOTAIR is overexpressed in HCC cells and tissues [ 24 27 ] and is associated with worse prognosis, shorter recurrence-free survival, and increased risk of recurrence after hepatic transplantation [ 26 , 28 , 29 ]. Functionally, HOTAIR enhances proliferation, migration, glycolysis, autophagy, and chemoresistance in HCC cells ( Table 1 ).…”
Section: Upregulated/oncogenic Lncrnas In Hccmentioning
confidence: 99%
“…[37][38][39] In this study, 17 articles with 20 studies were examined to study the role of HOTAIR in the diagnosis of different types of cancer, including GC, GBM, ESCC, NSCLC, Many studies also provided evidence that HOTAIR could be a promising diagnostic biomarker for cancer. 20,22,40,41 A study showed that the expression of plasma HOTAIR increased significantly in patients with BC. 40 Higher levels of plasma HOTAIR were found in patients with GC with 88% sensitivity and 84% specificity; additionally, an increased levels of HOTAIR was associated with advanced tumor stages and metastasis.…”
Section: Discussionmentioning
confidence: 99%